Solid electrolyte, electrochemical cell including solid electrolyte, and method for preparing solid electrolyte
By using solid electrolytes with sulfhydryl silver germanium ore crystal structure in all-solid secondary batteries and adjusting the mixing ratio of halogen atoms, the problem of poor oxidation stability of the battery at high voltage is solved, and better cycling characteristics and safety are achieved performance.
Patent Information
- Application Number
- CN202411464057.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-06
- Filing Date
- 2020-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
Existing all-solid-state secondary batteries have poor oxidation stability at high voltages, which poses safety risks.
A solid electrolyte with a sulfhydryl silver germanium ore crystal structure is used to improve the oxidation stability and ionic conductivity of the electrolyte by adjusting the mixing ratio of halogen atoms.
The oxidation stability of solid electrolytes is significantly improved at high voltages, and the cycle characteristics and safety performance of electrochemical cells are improved.
Smart Images

Figure CN119461273A_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese invention application (invention name: solid electrolyte, electrochemical cell including solid electrolyte, and method for preparing solid electrolyte, application date: October 30, 2020; application number: 202011191799.9).
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims priority to and the benefits of Korean Patent Application No. 10-2019-0140946, filed on November 6, 2019 in the Korean Intellectual Property Office, and all rights arising therefrom, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0004] The present disclosure relates to solid electrolytes, electrochemical cells including the solid electrolytes, and methods of making the solid electrolytes. Background Art
[0005] Recently, due to industrial demand, the development of batteries with high energy density and improved safety has become increasingly important. For example, lithium-ion batteries have been put into practical use in automobiles, and in information-related devices and communication equipment. Safety protection is particularly important in the automotive field because the protection involves protecting human life.
[0006] Commercially available lithium-ion batteries use a liquid electrolyte containing a flammable organic solvent, and therefore, there is a possibility of overheating and catching fire when a short circuit occurs. For this reason, an all-solid-state battery using a solid electrolyte instead of an electrolyte solution is desired.
[0007] When an all-solid-state secondary battery does not use a flammable organic solvent, the possibility of fire or explosion can be greatly reduced, even when a short circuit occurs. Therefore, such an all-solid-state secondary battery can be significantly safer than a lithium-ion battery using a liquid electrolyte.
[0008] Sulfide-based solid electrolytes used as solid electrolytes in all-solid-state secondary batteries may have excellent ionic conductivity. However, sulfide-based solid electrolytes have poor oxidation stability at high potentials, and therefore, there is still a need for solid electrolytes with improved oxidation stability. Summary of the invention
[0009] Provided are solid electrolytes having improved oxidation stability at high voltages.
[0010] Provided is an electrochemical cell including the solid electrolyte and having improved cycle characteristics.
[0011] A method for preparing the solid electrolyte is provided.
[0012] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description.
[0013] According to one aspect, a solid electrolyte includes: a compound having an argyrodite crystal structure and represented by Formula 1,
[0014] Formula 1
[0015] Li a M x PS b Br c X d
[0016] Among them, in formula 1,
[0017] M is Na, K, Fe, Mg, Ca, Ag, Cu, Zr, Zn, or a combination thereof;
[0018] X is Cl, I, or a combination thereof; and
[0019] 0≤x<1, 5≤(a+x)<7, 5≤a≤6, 4≤b≤6, 0<(c+d)≤2, and (c / d)>4.
[0020] According to one aspect, an electrochemical cell includes: a positive electrode layer; a negative electrode layer; and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, wherein the solid electrolyte layer includes the solid electrolyte.
[0021] According to one aspect, a method for preparing a solid electrolyte includes: providing a precursor mixture including a phosphorus (P) precursor, a sulfur (S) precursor, a bromine (Br) precursor, and an X precursor, wherein the X precursor includes Cl, I, or a combination thereof; reacting the precursor mixture to form a solid electrolyte precursor; and
[0022] heat-treating the solid electrolyte precursor at a temperature of about 200° C. to about 1000° C. to prepare the solid electrolyte,
[0023] The solid electrolyte is a compound having a argyrodite crystal structure and represented by Formula 1:
[0024] Li a M x PS b Br c X d
[0025] Among them, in formula 1,
[0026] M is Na, K, Fe, Mg, Ca, Ag, Cu, Zr, Zn, or a combination thereof;
[0027] X is Cl, I, or a combination thereof, and
[0028] 0≤x<1, 5≤(a+x)<7, 5≤a≤6, 4≤b≤6, 0<(c+d)≤2, and (c / d)>4.
[0029] According to one aspect, heat treating the solid electrolyte precursor is at a temperature of about 350°C to about 550°C.
[0030] An M precursor may be added to the precursor mixture, wherein M includes sodium (Na), potassium (K), iron (Fe), magnesium (Mg), calcium (Ca), silver (Ag), copper (Cu), zirconium (Zr), zinc (Zn), or a combination thereof.
[0031] According to one aspect, a solid electrolyte comprises:
[0032] a compound having an argyrodite crystal structure and represented by Formula 1; and
[0033] A compound having an argyrodite crystal structure and represented by Formula 6,
[0034] Formula 1
[0035] Li a M x PS b Br c X d
[0036] Among them, in formula 1,
[0037] M is Na, K, Fe, Mg, Ca, Ag, Cu, Zr, Zn, or a combination thereof,
[0038] X is Cl, I, or a combination thereof, and
[0039] 0≤x<1, 5≤(a+x)<7, 5≤a≤6, 4≤b≤6, 0<(c+d)≤2, and (c / d)>4,
[0040] Formula 6
[0041] Li 12-n-x AX 6-x Y′ x
[0042] Among them, in formula 6,
[0043] A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb, or Ta,
[0044] X is S, Se, or Te,
[0045] Y′ is Cl, Br, I, F, CN, OCN, SCN, or N3, and
[0046] 0 < x < 2, and 2 ≤ n ≤ 6. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The above and other aspects, features, and advantages of some embodiments of the present disclosure will become more apparent from the following description taken in conjunction with the accompanying drawings, in which:
[0048] Figure 1A is a graph of the intensity in arbitrary units (a.u.) versus the diffraction angle (°, 2θ) of the solid electrolytes prepared in Example 1 and Comparative Examples 1 to 5 when analyzed by X-ray diffraction using Cu Kα radiation;
[0049] Figure 1B and 1C are each Figure 1A an enlarged view of a part of;
[0050] Figure 2 is a graph of the specific capacity (milliamperes-hour per gram (mAh / g)) and the capacity recovery rate (%) versus (Li 5.45 Na 0.05 )PS 4.5 Cl 1.5- x Br x in x, which shows the charge and discharge characteristics of the all-solid-state secondary batteries of Examples 6 to 10 and Comparative Examples 8 to 12;
[0051] Figure 3 is a graph of voltage (V) versus capacity (mAh / g), which shows the charge and discharge characteristics of the all-solid-state secondary batteries of Example 10 and Comparative Example 13;
[0052] Figure 4 is a graph of capacity (mAh / g) versus the number of cycles, which shows the cycle characteristics of the all-solid-state secondary batteries of Example 10 and Comparative Example 13;
[0053] Figure 5 is a graph of voltage (V) versus capacity (mAh / g), which shows the charge and discharge characteristics of the all-solid-state battery of Example 10 and Comparative Example 14;
[0054] Figure 6 shows the capacity recovery rate of the all-solid-state secondary battery of Example 10 and Comparative Example 14; and
[0055] Figures 7 to 9 is a cross-sectional view illustrating the structure of the all-solid-state secondary battery. DETAILED DESCRIPTION
[0056] Embodiments will now be described in detail, and examples thereof are illustrated in the accompanying drawings, wherein the same reference numerals always refer to the same elements. In this regard, the present embodiment may have different forms and should not be construed as being limited to the descriptions set forth herein. Therefore, the following describes embodiments to illustrate aspects only by reference to the accompanying drawings. As used herein, the term "and / or" includes any and all combinations of one or more of the related enumerated items. Expressions such as "at least one (kind) of" when before or after the list of elements modify the entire list of elements and do not modify the individual elements of the list. As used herein, "one (kind) (indefinite article) (a, an)", "the (the)" and "at least one (kind)" do not represent the limitation of quantity, and are intended to include both the singular and the plural, unless the context clearly states otherwise. For example, "(an) element" has the same meaning as "at least one element", unless the context clearly states otherwise. "At least one (kind)" will not be construed as limiting "one (kind)". "Or" means "and / or".
[0057] It will be understood that when an element is referred to as being “on” another element, it can be directly on the other element or intervening elements may be present therebetween. In contrast, when an element is referred to as being “directly on” another element, there are no intervening elements present.
[0058] It will be understood that although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings herein, the "first element", "component", "region", "layer" or "part" discussed below may be referred to as a second element, component, region, layer or part.
[0059] The terms used herein are only for the purpose of describing specific embodiments and are not intended to be limiting. It will be understood that the terms "comprise" or "include" when used in this specification indicate the presence of stated features, regions, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more additional features, regions, wholes, steps, operations, elements, components and / or their collections.
[0060] In addition, relative terms such as "lower" or "bottom" and "upper" or "top" may be used herein to describe the relationship of one element to another element as shown in the figure. It will be understood that, in addition to the orientation shown in the figure, relative terms are also intended to include different orientations of the device. For example, if the device in one of the figures is turned over, the element described as being on the "lower" side of the other element will be oriented on the "upper" side of the other element. Therefore, depending on the specific orientation of the figure, the exemplary term "lower" may include both "lower" and "upper" orientations. Similarly, if the device in one of the figures is turned over, the element described as "below" or "below" the other element will be oriented "above" the other element. Therefore, the exemplary terms "below..." or "below..." may include both "above..." and "below..." orientations.
[0061] As used herein, "about" or "approximately" includes the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (e.g., limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, 20%, 10%, or 5% relative to the stated value.
[0062] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and the present disclosure, and will not be interpreted in an idealized or overly formal sense unless clearly so defined herein.
[0063] Exemplary embodiments are described herein with reference to cross-sectional views as schematic diagrams of idealized embodiments. Thus, deviations from the shapes of the figures as a result of, for example, manufacturing techniques and / or tolerances are to be expected. Therefore, the embodiments described herein should not be construed as being limited to the specific shapes of the regions as illustrated herein, but rather include deviations in shape caused by, for example, manufacturing. For example, a region illustrated or described as flat may typically have rough and / or nonlinear features. Moreover, the illustrated sharp corners may be rounded. Therefore, the regions illustrated in the figures are schematic in nature and their shapes are not intended to illustrate the precise shapes of the regions and are not intended to limit the scope of the claims.
[0064] As used herein, "argyrodite structure" or "argyrodite crystal structure" means that a compound has a structure isostructural to argyrodite Ag8GeS6.
[0065] The C rate refers to the current at which the battery will be discharged in 1 hour, for example, a battery with a discharge capacity of 1.6 ampere-hours would have a C rate of 1.6 amperes.
[0066] Hereinafter, a solid electrolyte, an electrochemical cell including a solid electrolyte layer including the solid electrolyte, and a method of preparing the solid electrolyte will be described in further detail.
[0067] A solid electrolyte is provided, including a compound having an argyrodite crystal structure and represented by Formula 1.
[0068] Formula 1
[0069] Li a M x PS b Br c X d
[0070] In Formula 1, M is sodium (Na), potassium (K), iron (Fe), magnesium (Mg), calcium (Ca), silver (Ag), copper (Cu), zirconium (Zr), zinc (Zn), or a combination thereof; X is chlorine (Cl), iodine (I), or a combination thereof; and 0≤x<1 and 5≤(a+x)<7, 5≤a≤6, 4≤b≤6, and 0<(c+d)≤2, (c / d)>4, c>0, and d>0.
[0071] In Formula 1, 5≤(a+x)≤6. In Formula 1, 0≤x≤0.07, for example, x is about 0.01 to about 0.06, for example, about 0.02 to about 0.05.
[0072] In Formula 1, (c / d) is 5 or more, for example, about 5 to about 199, for example, about 5 to about 125, for example, about 5 to about 20, for example, about 5 to about 14, for example, about 8 to about 14. In Formula 1, 5≤(a+x)≤6.
[0073] In order to provide an all-solid-state secondary battery with high energy density, a solid electrolyte having both high ionic conductivity and stability at high voltage is desired. Although argyrodite-based solid electrolytes may have excellent ionic conductivity, the oxidation stability at high voltage is not satisfactory, and therefore, an improved solid electrolyte is desired.
[0074] The present inventors have surprisingly found a solid electrolyte having excellent ionic conductivity and improved oxidation stability at high voltage by selecting the mixing ratio of halogen atoms in an argyrodite-based solid electrolyte.
[0075] In one aspect, X in Formula 1 is Cl. The argyrodite-based solid electrolyte according to an embodiment may be, for example, a compound represented by Formula 2.
[0076] Formula 2
[0077] Li a M x PS b Br c Cl d
[0078] In Formula 2, M is Na, K, Fe, Mg, Ca, Ag, Cu, Zr, Zn, or a combination thereof, 0 ≤ x ≤ 0.07, 5 ≤ a ≤ 6, 4 ≤ b ≤ 6, and 0 < (c + d) ≤ 2, 5 ≤ (a + x) ≤ 6, and (c / d) > 4.
[0079] The thiogermanate-based solid electrolyte may be a sulfide-based solid electrolyte.
[0080] In one aspect, 0 ≤ x ≤ 0.07. In one aspect, X in the compound represented by Formula 1 is Cl, 0 ≤ x ≤ 0.07, and 5 ≤ (a + x) ≤ 6.
[0081] The compound represented by Formula 1 may be the compound represented by Formula 3.
[0082] Formula 3
[0083] (Li 1-x1 M x1 ) 7-y PS 6-y (Br 1-x2 Cl x2 ) y
[0084] In Formula 3, M is Na, K, Fe, Mg, Ca, Ag, Cu, Zr, Zn, or a combination thereof, and 0 ≤ x1 < 1, 0 < x2 < 1, and 0 ≤ y ≤ 2.
[0085] In one aspect, in the compound represented by Formula 3, M is Na, K, or a combination thereof.
[0086] The compound represented by Formula 1 may be the compound represented by Formula 4 or the compound represented by Formula 5.
[0087] Formula 4
[0088] (Li 1-x1 Na x1 ) 7-y PS 6-y (Br 1-x2 Cl x2 ) y
[0089] In Formula 4, 0 ≤ x1 < 1, 0 < x2 < 1, and 0 ≤ y ≤ 2.
[0090] Formula 5
[0091] (Li 1-x1 K x1 ) 7-y PS 6-y (Br 1-x2 Cl x2 ) y
[0092] In Formula 5, 0 ≤ x1 < 1, 0 < x2 < 1, and 0 ≤ y ≤ 2.
[0093] In Formulas 4 and 5, x1 is from about 0.01 to about 0.9, such as from about 0.02 to about 0.5, such as from about 0.03 to about 0.2, such as from about 0.03 to about 0.1, and x2 is from about 0.01 to about 0.9, such as from about 0.02 to about 0.8, such as from about 0.03 to about 0.5, such as from about 0.05 to about 0.4, such as from about 0.06 to about 0.2.
[0094] The compound represented by Formula 1 can be, for example, Li 5.45 Na 0.05 PS 4.5 Cl 0.25 Br 1.25 、Li 5.5 PS 4.5 Cl 0.25 Br 1.25 、Li 5.45 Na 0.05 PS 4.5 Cl 0.1 Br 1.4 、Li 5.5 PS 4.5 Cl 0.1 Br 1.4 、Li 4.95 Na 0.05 PS4Cl 0.01 Br 1.99 、Li 5.74 PS 4.74 Cl 0.01 Br 1.25 、Li5PS4Cl 0.01 Br 1.99 、Li 5.45 K 0.05 PS 4.5 Cl 0.25 Br 1.25 、Li 5.45 K 0.05 PS 4.5 Cl 0.1 Br 1.4 、Li 4.95 K 0.05PS4Cl 0.01 Br 1.99 , Li 5.45 Na 0.05 PS 4.5 Cl 1.5 、(Li 5.45 Na 0.05 )PS 4.5 Cl 0.25 Br 1.25 , or a combination thereof.
[0095] When analyzed by X-ray diffraction using CuKα radiation, the compound of Formula 1 has a first peak at 2θ=29.82°±0.05° corresponding to the (311) crystal plane, and a second peak at 2θ=31.18°±0.05° corresponding to the (222) crystal plane. In addition, when analyzed by X-ray diffraction using CuKα radiation, the compound of Formula 1 may exhibit a third peak at 44.62°±0.11°2θ corresponding to the (422) crystal plane, a fourth peak at 47.47°±0.12°2θ corresponding to the (511) crystal plane, and a fifth peak at 51.99°±0.1°2θ corresponding to the (440) crystal plane.
[0096] The solid electrolyte according to the embodiment has an ionic conductivity of about 1 millisiemens / cm (mS / cm) or more, about 1.3 mS / cm or more, about 1.6 mS / cm or more, about 2 mS / cm or more, about 2 mS / cm to about 20 mS / cm, about 3 mS / cm to about 17 mS / cm, about 4 mS / cm to about 15 mS / cm, or about 6 mS / cm to about 10 mS / cm at 25° C. When the solid electrolyte has a high ionic conductivity of about 1 mS / cm or more, the solid electrolyte can be used as an electrolyte of an electrochemical cell.
[0097] The electrochemical cell may be, but is not limited to, an all-solid-state secondary battery or a lithium-air battery. The solid electrolyte may be used to provide any suitable electrochemical cell.
[0098] An electrochemical cell according to an embodiment includes: a positive electrode layer; a negative electrode layer; and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, wherein the solid electrolyte layer includes the solid electrolyte. When the solid electrolyte layer includes the solid electrolyte, a side reaction with lithium metal included in the negative electrode layer is suppressed, and thus, the cycle characteristics of the electrochemical cell are improved. The electrochemical cell may be an all-solid-state secondary battery.
[0099] In the electrochemical cell according to the embodiment, the positive electrode layer includes a solid electrolyte including a compound represented by Formula 1 having an argyrodite crystal structure.
[0100] Formula 1
[0101] Li a M x PS b Br c X d
[0102] In Formula 1, M is sodium (Na), potassium (K), iron (Fe), magnesium (Mg), calcium (Ca), silver (Ag), copper (Cu), zirconium (Zr), zinc (Zn), or a combination thereof, X is chlorine (Cl), iodine (I), or a combination thereof, 0≤x<1 and 5≤(a+x)<7, 5≤a≤6, 4≤b≤6, 0<(c+d)≤2, and (c / d)>4.
[0103] When the positive electrode layer includes the solid electrolyte according to an embodiment, lithium ion conductivity of the electrochemical cell and stability of the electrochemical cell with respect to lithium metal are improved. The solid electrolyte may serve as an ion conductor.
[0104] The content of the solid electrolyte in the positive electrode layer is about 2 parts by weight to about 70 parts by weight, such as about 3 parts by weight to about 30 parts by weight, or about 5 parts by weight to about 15 parts by weight, based on 100 parts by weight of the positive electrode active material. When the content of the solid electrolyte in the positive electrode layer is within this range, the stability of the electrochemical cell at high voltage is improved.
[0105] In one aspect, the content of the solid electrolyte in the positive electrode layer is from about 2 parts by weight to about 70 parts by weight, such as from about 3 parts by weight to about 30 parts by weight, or from about 5 parts by weight to about 15 parts by weight, based on 100 parts by weight of the positive electrode layer. When the content of the solid electrolyte in the positive electrode layer is within these ranges, the stability of the electrochemical cell at high voltage is improved.
[0106] After the all-solid-state secondary battery is charged to 4.25 volts and placed at 45° C. or 60° C. and then discharged, the all-solid-state secondary battery has a capacity recovery rate of about 65% to 100%, for example, about 85% to 100%.
[0107] For example, when the electrochemical cell is charged to 4 volts (V) or more, for example, charged to between 4V and 5V, placed at 45°C for 40 hours or at 60°C for 10 days, initially discharged, charged, and then further discharged, the capacity recovery rate of the electrochemical cell is about 65% to about 100%, about 70% to about 100%, about 75% to about 99%, 85% to about 99%, or about 89% to about 99%. For example, when the electrochemical cell is charged to 4.25V and kept at 45°C for 40 hours in a constant voltage (CV) state, initially discharged, charged, and then further discharged, the capacity recovery rate of the electrochemical cell is about 70% or more, about 85% or more, for example, about 89% or more, for example, about 85% to about 100%, or about 89% to about 99%. In addition, when the electrochemical cell is charged to 4.25V-5V, placed at 60°C for 10 days, initially discharged, charged, and then further discharged, the capacity recovery rate of the electrochemical cell is about 70% or more, about 85% or more, such as about 87% or more, such as about 85% to about 100%, or about 89% to about 99%. In one aspect, the electrochemical cell can be charged to a voltage between 4V and 5V, placed at a temperature between 40°C and 80°C for 1 day (24 hours) to 10 days, then initially discharged, charged, and further discharged to analyze the capacity recovery rate of the electrochemical cell.
[0108] The all-solid-state secondary battery among the electrochemical cells will be described in further detail.
[0109] refer to Figures 7 to 9 The all-solid-state secondary battery 1 includes: a negative electrode layer 20 including a negative electrode current collector 21 and a first negative electrode active material layer 22, a positive electrode layer 10 including a positive electrode active material layer 12, and a solid electrolyte layer 30 between the negative electrode layer 20 and the positive electrode layer 10. The positive electrode layer 10 may include a solid electrolyte according to an embodiment. For example, the positive electrode layer 10 includes a positive electrode active material, a solid electrolyte, and a conductive material.
[0110] Negative electrode layer
[0111] refer to Figures 7 to 9 The negative electrode layer 20 includes a negative electrode current collector 21 and a first negative electrode active material layer 22 , and the first negative electrode active material layer 22 includes a negative electrode active material.
[0112] The negative electrode active material included in the first negative electrode active material layer 22 may be in the form of particles. The average particle diameter of the negative electrode active material in the form of particles is, for example, about 4 μm or less, about 3 μm or less, about 2 μm or less, about 1 μm or less, or about 900 nm or less. The average particle diameter of the negative electrode active material in the form of particles is, for example, about 10 nm to about 4 μm, about 11 nm to about 3 μm, about 12 nm to about 2 μm, about 13 nm to about 1 μm, or about 14 nm to about 900 nm. When the average particle diameter of the negative electrode active material is within these ranges, reversible absorption and desorption of lithium during charging and discharging can easily occur. The average particle diameter of the negative electrode active material is, for example, a median diameter (D50) measured using a laser particle size distribution analyzer.
[0113] The negative electrode active material included in the first negative electrode active material layer includes a carbon negative electrode active material, a metal negative electrode active material, a metalloid negative electrode active material, or a combination thereof.
[0114] The carbon negative electrode active material may be amorphous carbon. Examples of the amorphous carbon may include, but are not limited to, carbon black (CB), acetylene black (AB), furnace black (FB), Ketjen black (KB), or graphene. Any suitable amorphous carbon may be used. Amorphous carbon, which is carbon having no crystallinity or low crystallinity, is distinguished from crystalline carbon or graphite-based carbon.
[0115] The metal or metalloid negative electrode active material may include, but is not limited to, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), or a combination thereof. Any suitable metal or metalloid negative electrode active material may be used as long as it is a material that can form an alloy or compound with lithium. For example, nickel (Ni) is not a metal negative electrode active material because it does not form an alloy with lithium.
[0116] The first negative electrode active material layer 22 includes one of these negative electrode active materials or includes a mixture of multiple different negative electrode active materials. For example, the first negative electrode active material layer 22 may include only amorphous carbon, or may include gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), or a combination thereof. In addition, the first negative electrode active material layer 22 may include a mixture of amorphous carbon and gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), or a combination thereof. The weight ratio of amorphous carbon to gold in the mixture of amorphous carbon and gold is, for example, about 10:1 to about 1:2, about 5:1 to about 1:1, or about 4:1 to about 2:1, but is not limited thereto. Its ratio can be selected according to the desired characteristics of the all-solid-state secondary battery 1. When the negative electrode active material has such a composition, the cycle characteristics of the all-solid-state secondary battery 1 are improved.
[0117] The negative electrode active material included in the first negative electrode active material layer includes a mixture of first particles of amorphous carbon and second particles of metal or metalloid. Examples of the metal or metalloid include gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) or zinc (Zn). The metalloid is also a semiconductor. The content of the second particle is about 8 weight percent (wt%) to about 60 weight %, about 10 weight % to about 50 weight %, about 15 weight % to about 40 weight % or about 20 weight % to about 30 weight %. When the content of the second particle is within this range, for example, the cycle characteristics of the all-solid-state secondary battery are improved.
[0118] The first negative electrode active material layer 22 includes a binder. Examples of the binder may include, but are not limited to, styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, or polymethyl methacrylate. Any suitable binder may be used. The binder may be used alone or as a plurality of different binders.
[0119] When the first negative active material layer 22 includes a binder, the first negative active material layer 22 is stabilized on the negative current collector 21. Cracks in the first negative active material layer 22 are suppressed during the charge-discharge process despite the volume change and / or relative position change of the first negative active material layer 22. For example, when the first negative active material layer 22 does not include a binder, the first negative active material layer 22 can be easily separated from the negative current collector 21. The portion of the first negative active material layer 22 separated from the negative current collector 21 exposes the negative current collector to contact the solid electrolyte layer 30, thereby increasing the possibility of a short circuit. The first negative active material layer 22 is manufactured by applying a slurry in which the material of the first negative active material layer 22 is dispersed on the negative current collector 21, and drying the slurry. The binder is included in the first negative active material layer 22, thereby enabling stable dispersion of the negative active material in the slurry. For example, when the slurry is applied to the negative electrode collector 21 by screen printing, clogging of the screen (eg, clogging of the screen due to agglomerates of the negative electrode active material) may be prevented.
[0120] The thickness d22 of the first negative electrode active material layer is about 50% or less, about 40% or less, about 30% or less, about 20% or less, about 10% or less, or about 5% or less of the thickness d12 of the positive electrode active material layer. The thickness d22 of the first negative electrode active material layer is about 1 μm to about 20 μm, about 2 μm to about 10 μm, or about 3 μm to about 7 μm. When the thickness d22 of the first negative electrode active material layer is less than these ranges, the lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode collector 21 disintegrate the first negative electrode active material layer 22, and thus, the cycle characteristics of the all-solid-state secondary battery 1 may be deteriorated. When the thickness d22 of the first negative electrode active material layer is greater than these ranges, the energy density of the all-solid-state secondary battery 1 is reduced, and the internal resistance of the all-solid-state secondary battery 1 due to the first negative electrode active material layer 22 increases. Therefore, if the first negative electrode active material is too thick, the cycle characteristics of the all-solid-state secondary battery 1 may be deteriorated.
[0121] When the thickness d22 of the first negative active material layer decreases, the charge capacity of the first negative active material layer 22 also decreases. The charge capacity of the first negative active material layer 22 is about 50% or less, about 40% or less, about 30% or less, about 20% or less, about 10% or less, about 5% or less, or about 2% or less of the charge capacity of the positive active material layer 12. For example, the charge capacity of the first negative active material layer 22 is about 0.1% to about 50%, about 0.2% to about 40%, about 0.3% to about 30%, about 0.4% to about 20%, about 0.5% to about 10%, or about 5% to about 10% of the charge capacity of the positive active material layer 12. When the charge capacity of the first negative electrode active material layer 22 is too small, the thickness of the first negative electrode active material layer 22 becomes too thin, so that the lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 cause the first negative electrode active material layer 22 to disintegrate, and thus, the cycle characteristics of the all-solid-state secondary battery 1 may deteriorate. When the charge capacity of the first negative electrode active material layer 22 increases to more than about 50%, the energy density of the all-solid-state secondary battery 1 decreases, and the internal resistance of the all-solid-state secondary battery 1 due to the first negative electrode active material layer 22 increases, which may deteriorate the cycle characteristics of the all-solid-state secondary battery 1.
[0122] The charge capacity of the positive electrode active material layer 12 can be obtained by multiplying the charge capacity (mAh / g) of the positive electrode active material by the mass of the positive electrode active material in the positive electrode active material layer 12. When several positive electrode active materials are used, the value of the charge capacity density multiplied by the mass is calculated for the positive electrode active material, and the sum of these values is called the charge capacity of the positive electrode active material layer 12. The charge capacity of the first negative electrode active material layer 22 is also calculated in the same manner. That is, the charge capacity of the first negative electrode active material layer 22 is obtained by multiplying the charge capacity (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the first negative electrode active material layer 22. When several negative electrode active materials are used, the value of the charge capacity density multiplied by the mass is calculated for the negative electrode active material, and the sum of these values is called the charge capacity of the first negative electrode active material layer 22. The charge capacity density of the positive electrode active material and the negative electrode active material is a capacity evaluated by using an all-solid-state half-cell using lithium metal as a counter electrode. The charge capacity of the positive active material layer 12 and the charge capacity of the first negative active material layer 22 can be directly measured by using the charge capacity measurement of the all-solid-state half-cell. When the measured charge capacity is divided by the mass of the active material, the charge capacity density is obtained. Alternatively, the charge capacity of the positive active material layer 12 and the charge capacity of the first negative active material layer 22 may be the initial charge capacity measured during the first cycle.
[0123] The negative electrode current collector 21 is made of, for example, a material that does not react with lithium, that is, a material that does not form an alloy or compound with lithium. Examples of materials constituting the negative electrode current collector 21 may include, but are not limited to, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), or nickel (Ni). Any suitable material may be used as the negative electrode current collector. The negative electrode current collector 21 may be made of one of the aforementioned metals, or may be made of two or more metals or coating materials. The negative electrode current collector 21 is manufactured in the form of a plate or foil.
[0124] The first negative electrode active material layer 22 may further include additives used in a conventional all-solid-state secondary battery 1 , such as a filler, a dispersant, an ion conductive material, and the like.
[0125] refer to Figure 8 , the all-solid-state secondary battery 1 further includes a thin film 24 on the negative electrode current collector 21, and the thin film 24 includes an element capable of forming an alloy with lithium. The thin film 24 is disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22. The thin film 24 includes, for example, an element capable of forming an alloy with lithium. Examples of the element capable of forming an alloy with lithium may include, but are not limited to, gold, silver, zinc, tin, indium, silicon, aluminum, or bismuth. Any suitable element may be used as long as it can form an alloy with lithium. The thin film 24 is made of one of these metals, or of an alloy of several metals. When the thin film 24 is disposed on the negative electrode current collector 21, for example, the second negative electrode active material layer (not shown) deposited between the thin film 24 and the first negative electrode active material layer 22 is further flattened, and therefore, the cycle characteristics of the all-solid-state secondary battery 1 can be improved.
[0126] The thickness d24 of the film is, for example, about 1 nm to about 800 nm, about 10 nm to about 700 nm, about 50 nm to about 600 nm, or about 100 nm to about 500 nm. When the thickness d24 of the film 24 is less than 1 nm, it may be difficult to present the function of the film 24. When the film 24 is too thick, the film 24 itself absorbs lithium, so that the amount of lithium deposited in the negative electrode is reduced, thereby reducing the energy density of the all-solid-state battery and deteriorating the cycle characteristics of the all-solid-state secondary battery 1. The film 24 can be formed on the negative electrode collector 21 by vacuum deposition, sputtering or plating, but the method is not limited thereto. The film 24 can be formed by any suitable method.
[0127] refer to Fig. 9, the all-solid-state secondary battery 1 further includes a second negative electrode active material layer 23 disposed between the negative electrode collector 21 and the solid electrolyte layer 30 by charging. For example, the all-solid-state secondary battery 1 further includes a second negative electrode active material layer 23 disposed between the negative electrode collector 21 and the first negative electrode active material layer 22 during charging of the all-solid-state secondary battery. Although not shown in the figure, the all-solid-state secondary battery 1 further includes a second negative electrode active material layer disposed between the solid electrolyte layer 30 and the first negative electrode active material layer 22 by charging. Although not shown in the figure, the all-solid-state secondary battery 1 further includes a second negative electrode active material layer disposed in the first negative electrode active material layer 22 during charging of the all-solid-state secondary battery.
[0128] The second negative electrode active material layer 23 is a metal layer including lithium or a lithium alloy. Therefore, when the second negative electrode active material layer 23 is a metal layer including lithium, the second negative electrode active material layer 23 acts as a lithium reservoir. Examples of the lithium alloy may include, but are not limited to, Li-Al alloy, Li-Sn alloy, Li-In alloy, Li-Ag alloy, Li-Au alloy, Li-Zn alloy, Li-Ge alloy, or Li-Si alloy. Any suitable lithium alloy may be used. The second negative electrode active material layer 23 may be made of one of these alloys or lithium, or may be made of several alloys.
[0129] The thickness d23 of the second negative electrode active material layer is not limited, but is, for example, about 1 μm to about 1000 μm, about 2 μm to about 500 μm, about 3 μm to about 200 μm, about 4 μm to about 150 μm, about 5 μm to about 100 μm, or about 1 μm to about 50 μm. When the thickness d23 of the second negative electrode active material layer is too thin, the second negative electrode active material layer 23 is difficult to use as a lithium reservoir. When the thickness d23 of the second negative electrode active material layer is too thick, the mass and volume of the all-solid-state secondary battery 1 may increase and its cycle characteristics may deteriorate. The second negative electrode active material layer 23 may be, for example, a metal foil having a thickness within this range.
[0130] In the all-solid-state secondary battery 1, the second negative electrode active material layer 23 is arranged between the negative electrode collector 21 and the first negative electrode active material layer 22 before assembling the all-solid-state secondary battery 1, or is deposited between the negative electrode collector 21 and the first negative electrode active material layer 22 during charging after assembling the all-solid-state secondary battery 1.
[0131] When the second negative electrode active material layer 23 is disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before assembling the all-solid-state secondary battery 1, the second negative electrode active material layer 23 acts as a lithium reservoir because the second negative electrode active material layer 23 is a metal layer including lithium. Therefore, the cycle characteristics of the all-solid-state secondary battery 1 including the second negative electrode active material layer 23 are improved. For example, a lithium foil is disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before assembling the all-solid-state secondary battery 1.
[0132] When the second negative electrode active material layer 23 is provided during charging after the assembly of the all-solid-state secondary battery 1, the second negative electrode active material layer 23 is not included during the assembly of the all-solid-state secondary battery 1, and therefore, the energy density of the all-solid-state secondary battery 1 increases. For example, during the charging of the all-solid-state secondary battery 1, the all-solid-state secondary battery 1 is charged to exceed the charging capacity of the first negative electrode active material layer 22. That is, the first negative electrode active material layer 22 is overcharged. In the initial stage of charging, lithium is absorbed in the first negative electrode active material layer 22. That is, the negative electrode active material included in the first negative electrode active material layer 22 forms an alloy or compound with lithium ions migrated from the positive electrode layer 10. When the all-solid-state secondary battery 1 is charged to exceed the charging capacity of the first negative electrode active material layer 22, lithium is deposited on the back of the first negative electrode active material layer 22, that is, between the negative electrode collector 21 and the first negative electrode active material layer 22, and the material corresponding to the second negative electrode active material layer 23 is formed by the deposited lithium. The second negative electrode active material layer 23 is a metal layer mainly including lithium (ie, lithium metal). This result is obtained as follows: the negative electrode active material included in the first negative electrode active material layer 22 includes a material that forms an alloy or a compound with lithium. During discharge, the lithium in the first negative electrode active material layer 22 and the second negative electrode active material layer 23 (ie, the metal layer) is ionized to move toward the positive electrode layer 10. Therefore, lithium can be used as the negative electrode active material in the all-solid-state secondary battery 1. When the first negative electrode active material layer 22 covers the second negative electrode active material layer 23, the first negative electrode active material layer 22 serves as a protective layer for the second negative electrode active material layer 23, i.e., the metal layer, and for suppressing the deposition and growth of lithium dendrites. Therefore, the short circuit and capacity reduction of the all-solid-state battery 1 are suppressed, and as a result, the cycle characteristics of the all-solid-state secondary battery 1 are improved. In addition, when the second negative electrode active material layer 23 is deposited during charging after assembly of the all-solid-state secondary battery 1, the negative electrode collector 21, the first negative electrode active material layer 22, and the area between the negative electrode collector 21 and the first negative electrode active material layer 22 are Li-free areas, meaning that lithium (Li) metal or lithium (Li alloy) is not included in the initial state or discharge state of the all-solid-state secondary battery.
[0133] The all-solid secondary battery 1 has a structure in which the second negative electrode active material layer 23 is provided on the negative electrode collector 21, and the solid electrolyte layer 30 is directly provided on the second negative electrode active material layer 23. The second negative electrode active material layer 23 is a lithium metal layer or a lithium alloy layer.
[0134] When the solid electrolyte layer 30 includes the sulfide-based solid electrolyte, a side reaction between the second negative electrode active material layer 23 (lithium metal layer) and the solid electrolyte layer 30 is suppressed, and thus the cycle characteristics of the all-solid-state secondary battery 1 are improved.
[0135] Solid electrolyte layer
[0136] refer to Figures 7 to 9 The solid electrolyte layer 30 includes a solid electrolyte disposed between the negative electrode layer 20 and the positive electrode layer 10 .
[0137] In addition to the solid electrolyte according to the embodiment, the solid electrolyte layer may further include a commercially available sulfide-based solid electrolyte. The solid electrolyte may further include Li2S-P2S5, Li2S-P2S5-LiX (X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (m and n are each positive and Z is Ge, Zn, Ga, or a combination thereof), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (p and q are each positive numbers and M is P, Si, Ge, B, Al, Ga, In, or a combination thereof), or a combination thereof. The sulfide-based solid electrolyte further included in the solid electrolyte layer is amorphous, crystalline, or a mixed state thereof.
[0138] Commercially available sulfide-based solid electrolytes may include an argyrodite-type solid electrolyte represented by Formula 6.
[0139] Formula 6
[0140] Li 12-n-x AX 6-x Y′ x
[0141] In Formula 6, A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb, or Ta; X is S, Se, or Te; Y′ is Cl, Br, I, F, CN, OCN, SCN, or N3; 0 < x < 2; n is the oxidation number of A and 2 ≤ n ≤ 6.
[0142] The argyrodite-type solid electrolyte includes Li 7-x PS 6-x Cl x (0 < x < 2), Li 7-x PS 6-x Br x (0 < x < 2), Li 7- x PS 6-x I x (0 < x < 2), or a combination thereof. The argyrodite-type solid electrolyte may include Li6PS5Cl, Li6PS5Br, Li6PS5I, or a combination thereof.
[0143] The solid electrolyte layer 30 further includes a binder. Examples of the binder included in the solid electrolyte layer 30 include, but are not limited to, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, or polyethylene. Any suitable binder can be used. The binder of the solid electrolyte layer 30 can be the same as or different from the binders of the positive electrode active material layer 12 and the first negative electrode active material layer 22.
[0144] Positive electrode layer
[0145] The positive electrode layer 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12.
[0146] As the positive electrode current collector 11, a plate or foil including indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof can be used. The positive electrode current collector 11 can be omitted.
[0147] The positive electrode active material layer 12 includes a positive electrode active material and a solid electrolyte. The solid electrolyte included in the positive electrode layer 10 is similar (the same) as or different from the solid electrolyte included in the solid electrolyte layer 30. For details of the solid electrolyte, refer to the solid electrolyte layer 30. According to an embodiment, the solid electrolyte contains the solid electrolyte according to the present invention.
[0148] The positive electrode layer includes a positive electrode active material, and the positive electrode active material is a compound that can reversibly absorb and desorb lithium ions. The compound includes a lithium transition metal oxide having a layered crystal structure, a lithium transition metal oxide having an olivine crystal structure, a lithium transition metal oxide having a spinel crystal structure, or a combination thereof. Examples of the positive electrode active material include, but are not limited to, lithium transition metal oxides such as lithium cobalt oxide (LCO), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt manganese oxide (NCM), lithium manganese oxide (lithium manganate), or lithium iron phosphate, nickel sulfide, copper sulfide, lithium sulfide, iron oxide, or vanadium oxide. Any suitable positive electrode active material can be used. The positive electrode active material can be used alone or as a mixture of two or more thereof.
[0149] As the positive electrode active material, for example, a compound represented by one of the following formulae may be used: Li a A 1-b B′ b D2 (where 0.90≤a≤1 and 0≤b≤0.5); Li a E 1-b B′ b O 2-c D c (where 0.90≤a≤1, 0≤b≤0.5, and 0≤c≤0.05); LiE 2-b B′ b O 4-c D c (where 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b-c Co b B′ c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Co b B′ c O 2-α F′ α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Co b B′ c O 2-α F′2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B′ c Dα (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Mn b B′ c O 2-α F′ α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b- c Mn b B′ c O 2-α F′2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni b E c G d O2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, and 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0.001≤e≤0.1); Li a NeG b O2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a CoG b O2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a MnG b O2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a Mn b O4 (where 0.90≤a≤1 and 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiI′O2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f)Fe2(PO4)3(0 ≤ f ≤ 2); or LiFePO4. In these compounds, A is Ni, Co, Mn, or a combination thereof; B′ is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D is O, F, S, P, or a combination thereof; E is Co, Mn, or a combination thereof; F′ is F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q is Ti, Mo, Mn, or a combination thereof; I′ is Cr, V, Fe, Sc, Y, or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof. In an embodiment, a compound having a coating layer on the surface of the compound may be used, or a mixture of the compound and a compound having a coating layer may be used. The coating layer formed on the surface of the compound may include a coating element compound such as an oxide of the coating element, a hydroxide of the coating element, a hydroxyoxide of the coating element, a carbonate oxide of the coating element, or a hydroxycarbonate of the coating element. The compound constituting the coating layer may be amorphous or crystalline. The coating layer may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof as the coating element. The method of forming the coating layer is selected within a range that does not adversely affect the physical properties of the positive electrode active material. The coating method is, for example, spraying or dip coating. Any suitable coating method may be used.
[0150] The positive electrode active material includes a lithium salt of a transition metal oxide having a layered rock salt structure. "Layered rock salt structure" refers to the following structure: wherein oxygen atom layers and metal atom layers are alternately and regularly arranged in the <111> direction of the cubic rock salt structure, and thus each of the atom layers forms a two-dimensional plane. "Cubic rock salt structure" refers to the sodium chloride (NaCl) type structure, which is a type of crystal structure, and more specifically, wherein face-centered cubic lattices (FCC) that form cations and anions, respectively, are arranged such that the unit cell (unit lattice) is offset by half of the ridge of the unit cell. The lithium transition metal oxide having such a layered rock salt structure is a ternary lithium transition metal oxide such as LiNi x Co y Al z O2 (NCA) or LiNi x Co y Mn z O2 (NCM) (0 < x < 1, 0 < y < 1, 0 < z < 1, (x + y + z) = 1). When the positive electrode active material includes a ternary lithium transition metal oxide having a layered rock salt structure, the energy density and thermal stability of the all-solid-state secondary battery 1 are improved.
[0151] The positive electrode active material may be covered by a coating layer as described. The coating layer may be any suitable coating layer for a positive electrode active material for an all-solid-state secondary battery. The coating layer is, for example, Li2O-ZrO2 (LZO).
[0152] When the positive electrode active material includes nickel (Ni) as a ternary lithium transition metal oxide such as NCA or NCM, the capacity density of the all-solid-state secondary battery 1 increases. As a result, the cycle characteristics of the all-solid-state secondary battery 1 improve.
[0153] The positive electrode active material is in the form of particles having a true spherical shape or an ellipsoidal shape. The particle diameter of the positive electrode active material is not limited and is within a suitable range in the positive electrode active material of the all-solid-state secondary battery. The content of the positive electrode active material of the positive electrode layer is also not limited and is within a suitable range in the positive electrode layer of the all-solid-state secondary battery.
[0154] In addition to the positive electrode active material and the solid electrolyte, the positive electrode layer 10 may further include additives such as conductive materials, binders, fillers, dispersants, or ion conductors. Examples of the conductive materials include graphite, carbon black, acetylene black, Ketjen black, carbon fibers, or metal powders. Examples of the binders include styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, or polyethylene. The fillers, dispersants, and ion conductors may be included in the positive electrode active material layer, and may be any suitable material for the electrode of the all-solid-state secondary battery.
[0155] A method of preparing a solid electrolyte according to another embodiment includes: providing a precursor mixture including a phosphorus (P) precursor, a sulfur (S) precursor, a bromine (Br) precursor, and an X precursor; and reacting the precursor mixture to prepare the solid electrolyte.
[0156] The phosphorus precursor is a compound containing phosphorus, and examples thereof include P2S5, red phosphorus, or white phosphorus. The sulfur precursor is a compound containing sulfur, or a compound containing sulfur and lithium, and examples thereof include Li2S.
[0157] In the X precursor, X is chlorine (Cl), iodine (I), or a combination thereof. The X precursor is a compound containing X and lithium, and examples thereof include lithium halides. The lithium halide is, for example, LiCl, LiI, or a combination thereof.
[0158] The bromine precursor is a compound including bromine and lithium, and examples thereof include LiBr.
[0159] An M precursor may be further added to the precursor mixture. In the M precursor, M is sodium (Na), potassium (K), iron (Fe), magnesium (Mg), calcium (Ca), silver (Ag), copper (Cu), zirconium (Zr), zinc (Zn), or a combination thereof. The M precursor is a compound containing M and sulfur. Examples of the M precursor include Na2S or K2S.
[0160] The step of reacting the precursor mixture to prepare the solid electrolyte may further include, for example, reacting the precursor mixture to form a solid electrolyte precursor, and heat treating the solid electrolyte precursor at a temperature of about 200°C to about 1000°C, for example, at a temperature of about 350°C to about 550°C.
[0161] The method for reacting the precursor mixture is not limited, but examples thereof include mechanical grinding (MM). For example, when mechanical grinding is used, the solid electrolyte precursor is prepared by stirring and reacting starting materials such as Li2S or P2S5 using a ball mill. Although the stirring speed and stirring time of mechanical grinding are not limited, the faster the stirring speed, the faster the generation rate of the solid electrolyte precursor, and the longer the stirring time, the higher the conversion rate of the raw material to the solid electrolyte precursor.
[0162] Subsequently, the solid electrolyte precursor obtained by mechanical grinding is heat treated at a predetermined temperature and then pulverized to prepare a granular solid electrolyte. When the solid electrolyte has a glass transition characteristic, the solid electrolyte can be changed from amorphous to crystalline. The heat treatment temperature is, for example, about 200°C to about 1000°C, about 250 to about 750°C, or about 350°C to about 550°C. When the heat treatment is implemented within these temperature ranges, a solid electrolyte with a uniform composition is formed.
[0163] The heat treatment time is selected based on the heat treatment temperature, for example, about 1 to about 100 hours, about 10 to about 80 hours, about 10 to about 50 hours, about 10 to about 30 hours, or about 10 hours to about 20 hours. The solid electrolyte formed by heat treatment for a time within these ranges has both excellent ionic conductivity and high temperature stability.
[0164] The heat treatment atmosphere is an inert atmosphere. The gas used in the heat treatment atmosphere is not limited to nitrogen or argon, and may be any suitable inert atmosphere gas.
[0165] The method of manufacturing an all-solid-state secondary battery according to an embodiment includes: preparing a solid electrolyte using the aforementioned method; forming a positive electrode layer 10 , a negative electrode layer 20 , and / or a solid electrolyte layer 30 using the solid electrolyte; and laminating these layers.
[0166] Solid electrolyte layer 30 has a thickness of about 10 μm to about 200 μm.
[0167] Preparation of negative electrode layer
[0168] The negative electrode active material, conductive material, binder, and solid electrolyte included in the first negative electrode active material layer 22 are added to a polar solvent or a non-polar solvent to prepare a slurry. The prepared slurry is applied to the negative electrode collector 21 and dried to prepare a first laminate. Subsequently, the first laminate is pressed to prepare the negative electrode layer 20. The pressing may be, but is not necessarily limited to, roll pressing, flat pressing, or hot pressing. Any suitable pressing method may be used. The pressing process may be omitted.
[0169] The negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer, wherein the first negative electrode active material layer includes a negative electrode active material and is disposed on the negative electrode current collector. The negative electrode active material includes a carbon negative electrode active material, a metal negative electrode active material, a semi-metal negative electrode active material, or a combination thereof. The carbon negative electrode active material includes amorphous carbon, crystalline carbon, or a combination thereof. The metal negative electrode active material or semi-metal negative electrode active material includes gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), or a combination thereof.
[0170] The negative electrode layer further includes a second negative electrode active material layer disposed between the negative electrode collector and the first negative electrode active material layer and / or between the solid electrolyte layer and the first negative electrode active material layer, and the second negative electrode active material layer is a metal layer including lithium or a lithium alloy.
[0171] Preparation of positive electrode layer
[0172] The positive electrode active material, conductive material, binder, and solid electrolyte included in the positive electrode active material layer 12 are added to a non-polar solvent to prepare a slurry. The prepared slurry is applied to the positive electrode collector 11 and dried to obtain a laminate. The obtained laminate is pressed to prepare the positive electrode layer 10. The pressing may be, but is not necessarily limited to, roll pressing, flat pressing, or hot pressing. Any suitable pressing method may be used. The pressing process may be omitted. Alternatively, the positive electrode layer 10 is prepared by compacting the mixture of materials constituting the positive electrode active material layer 12 into sheets (discs) or by stretching (extruding) the mixture into sheets. When the positive electrode layer 10 is prepared by this method, the positive electrode collector 11 may be omitted.
[0173] Preparation of solid electrolyte layer
[0174] The solid electrolyte layer 30 is formed by a solid electrolyte including the solid electrolyte material. For example, the solid electrolyte layer 30 is prepared by applying a mixture of a solid electrolyte, a solvent, and a binder, and drying and pressing the mixture. Alternatively, the solid electrolyte layer 30 is prepared by depositing the solid electrolyte obtained by the aforementioned preparation method using a suitable film forming method such as aerosol deposition, cold spraying, or sputtering. Alternatively, the solid electrolyte layer 30 is prepared by pressing solid electrolyte particles to form a film.
[0175] Manufacturing of all-solid-state secondary batteries
[0176] The positive electrode layer 10 , the negative electrode layer 20 , and the solid electrolyte layer 30 prepared by the aforementioned method are layered so that the solid electrolyte layer 30 is provided between the positive electrode layer 10 and the negative electrode layer 20 , and pressed to manufacture the all-solid secondary battery 1 .
[0177] For example, a solid electrolyte layer 30 is disposed on the positive electrode layer 10 to prepare a second stack. Subsequently, a negative electrode layer 20 is disposed on the second stack so that the solid electrolyte layer 30 contacts the first negative electrode active material layer to prepare a third stack, and the third stack is pressed to manufacture an all-solid-state secondary battery 1. The pressing is performed at a temperature of room temperature (about 20°C to about 25°C) to 90°C. Alternatively, the pressing is performed at a high temperature of 100°C or more. The pressing time is, for example, about 30 minutes (min) or less, about 20 minutes or less, about 15 minutes or less, or about 10 minutes or less. The pressing time is about 1 millisecond (ms) to about 30 minutes, about 1ms to about 20 minutes, about 1ms to about 15 minutes, or about 1ms to about 10 minutes. Examples of the pressing include, but are not limited to, isostatic pressing, roller pressing, or flat pressing. Any suitable pressing can be used. The pressure applied during pressing is, for example, about 500 MPa (MPa) or less, about 400 MPa or less, about 300 MPa or less, about 200 MPa or less, or about 100 MPa or less. The pressure applied during pressing is, for example, about 50 MPa to about 500 MPa, about 52 MPa to about 480 MPa, about 54 MPa to about 450 MPa, about 56 MPa to about 400 MPa, about 58 MPa to about 350 MPa, about 60 MPa to about 300 MPa, about 62 MPa to about 250 MPa, about 64 MPa to about 200 MPa, about 66 MPa to about 150 MPa, or about 68 MPa to about 100 MPa. Solid electrolyte powder is sintered to form a solid electrolyte layer by the pressing.
[0178] The configuration and manufacturing method of the foregoing all-solid-state secondary battery are exemplary embodiments, and structural components, manufacturing processes, and the like thereof may be appropriately changed.
[0179] Hereinafter, the method for preparing a solid electrolyte according to an embodiment will be described in further detail with reference to Examples and Comparative Examples.In addition, the following Examples are provided only for illustrative purposes, and the present disclosure is not limited to these Examples.
[0180] Example
[0181] Preparation of solid electrolyte
[0182] Example 1
[0183] After weighing Li2S, Na2S, P2S5, LiCl and LiBr to (Li 5.45 Na 0.05 )PS 4.5 Cl 0.25 Br 1.25 After the target composition of , a mechanical grinding process was performed in a ball mill using a high energy mill (Pulnerisette 7) for 20 hours to mix the components. The mechanical grinding process was performed at room temperature and under an argon atmosphere at a rotation speed of 380 rpm for 20 hours.
[0184] 300 mg of the composition (Li 5.45 Na 0.05 )PS 4.5 Cl 0.25 Br 1.25 The powder material was heat-treated at 450°C for 12 hours in a vacuum atmosphere to obtain a solid electrolyte.
[0185] Examples 2 and 3
[0186] The solid electrolyte was prepared in the same manner as in Example 1, except that the contents of Li2S, P2S5, LiCl, and LiBr were selected to a target composition of Li 5.5 PS 4.5 Cl 0.25 Br 1.25 and Li 5.5 PS 4.5 Cl 0.1 Br 1.4 , without using Na2S as the starting material.
[0187] Examples 4 and 5
[0188] The solid electrolyte was prepared in the same manner as in Example 1, except that the contents of Li2S, Na2S, P2S5, LiCl, and LiBr were selected to a target composition of Li 5.45 Na 0.05 PS 4.5 Cl 0.1 Br 1.4and Li 5.45 Na 0.05 PS 4.5 Cl 0.25 Br 1.25 , and the heat treatment temperature was changed from 450°C to 400°C.
[0189] Example 5A
[0190] A solid electrolyte was prepared in the same manner as in Example 1, except as follows: the contents of Li2S, Na2S, P2S5, LiCl, and LiBr were selected to obtain a solid electrolyte having the composition shown in Table 1.
[0191] Table 1
[0192] Example Solid electrolyte 5A-1 <![CDATA[Li 4.95 On 0.05 PS4Cl 0.01 No. 1.99 ]]> 5A-2 <![CDATA[Li 5.74 PS 4.74 Cl 0.01 Br 1.25 ]]> 5A-3 <![CDATA[Li 5.45 K 0.05 PS 4.5 Cl 0.25 Br 1.25 ]]> 5A-4 <![CDATA[Li 5.45 K 0.05 PS 4.5 Cl 0.1 Br 1.4 ]]>
[0193] Comparative Examples 1 to 7
[0194] A solid electrolyte was prepared in the same manner as in Example 1, except as follows: the contents of Li2S, Na2S, P2S5, LiCl, and LiBr were selected to obtain a solid electrolyte having the composition shown in Table 2.
[0195] Table 2
[0196] Example Solid electrolyte Comparative Example 1 <![CDATA[Li 5.45 In the 0.05 PS 4.5 Cl 1.5 ]]> Comparative Example 2 <![CDATA[Li 5.45 On 0.05 PS 4.5 Cl 1.25 No 0.25 ]]> Comparative Example 3 <![CDATA[Li 5.45 In the 0.05 PS 4.5 Cl1Br 0.5 ]]> Comparative Example 4 <![CDATA[Li 5.45 On 0.05 PS 4.5 Cl 0.75 No 0.75 ]]> Comparative Example 5 <![CDATA[Li 5.45 On 0.05 PS 4.5 Cl 0.5 Br1]]> Comparative Example 6 <![CDATA[(Li 5.6925 In the 0.0575 )PS 4.75 Cl 1.25 ]]> Comparative Example 7 <![CDATA[Li 5.75 PS 4.75 Cl 1.25 ]]> Comparative Example 7A <![CDATA[(Li 5.45 On 0.05 )P.S. 4.5 Cl 0.25 No 1.25 ]]>
[0197] Preparation Example 1
[0198] The positive electrode active material having aLi2O-ZrO2 coating film was prepared according to the method disclosed in Korean Patent Publication No. 10-2016-0064942 (the contents of which are incorporated herein by reference in their entirety), and was prepared according to the following method.
[0199] The positive electrode active material LiNi 0.8 Co 0.15 Mn 0.05 O2(NCM), lithium methoxide, zirconium propoxide, ethanol, and ethyl acetoacetate were stirred and mixed for 30 minutes to prepare an alcohol solution of aLi2O-ZrO2(a=1) (coating solution for aLi2O-ZrO2). The contents of lithium methoxide and zirconium propoxide were adjusted so that the content of aLi2O-ZrO2(a=1) applied on the surface of the positive electrode active material was 0.5 mol%.
[0200] Next, a coating solution for aLi2O-ZrO2 is mixed with the positive electrode active material to obtain a mixed solution, and the mixed solution is heated to about 40° C. while being stirred to evaporate and dry a solvent such as alcohol. The mixed solution is irradiated with ultrasonic waves.
[0201] In this process, the precursor of aLi2O-ZrO2 may be supported on the surface of the particles of the positive electrode active material.
[0202] The aLi2O-ZrO2 precursor supported on the surface of the particles of the positive electrode active material fine powder is heat-treated at about 350°C for 1 hour in an oxygen atmosphere. During the heat treatment process, the aLi2O-ZrO2 precursor present on the positive electrode active material becomes aLi2O-ZrO2 (a=1). The content of Li2O-ZrO2 (LZO) is about 0.4 parts by weight based on 100 parts by weight of LiNi 0.8 Co 0.15 Mn 0.05 O2(NCM).
[0203] According to the above preparation process, LiNi with aLi2O-ZrO2 coating film is obtained. 0.8 Co 0.15 Mn 0.05 O2(NCM). In aLi2O-ZrO2, a is 1.
[0204] Manufacturing of all-solid-state secondary batteries
[0205] Example 6
[0206] Preparation of positive electrode layer
[0207] As the positive electrode active material, LiNi coated with Li2O-ZrO2 (LZO) was obtained according to Preparation Example 1. 0.8 Co 0.15 Mn 0.05 O2(NCM).
[0208] As a solid electrolyte, the solid electrolyte powder prepared in Example 1 was prepared. As a binder, a polytetrafluoroethylene (PTFE) binder (Teflon binder manufactured by DuPont Corporation) was provided. As a conductive material, carbon nanofibers (CNF) were provided. These materials were mixed in a weight ratio of 84.2:11.5:2.9:1.4 of positive electrode active material: solid electrolyte: conductive material: binder to obtain a mixture, and the mixture was molded in the form of a sheet to prepare a positive electrode sheet. The prepared positive electrode sheet was pressed on a positive electrode current collector formed of a carbon-coated aluminum foil having a thickness of 18 μm to prepare a positive electrode layer. The thickness of the positive electrode active material layer included in the positive electrode layer is 100 μm.
[0209] Negative electrode layer
[0210] As the negative electrode layer, a lithium metal layer having a thickness of about 30 μm was used.
[0211] Solid electrolyte layer
[0212] 1 part by weight of styrene-butadiene rubber (SBR) is added to 100 parts by weight of a crystallized argyrodite-based solid electrolyte (Li6PS5Cl) to prepare a mixture. Xylene and diethylbenzene are added to the mixture and stirred to prepare a slurry. The prepared slurry is applied to a nonwoven fabric using a knife coater and dried at 40°C in air to obtain a laminate. The obtained laminate is dried at 40°C in a vacuum for 12 hours. A solid electrolyte layer is thus obtained.
[0213] Manufacturing of all-solid-state secondary batteries
[0214] A solid electrolyte layer is disposed on the negative electrode layer, and a positive electrode layer is disposed on the solid electrolyte layer to prepare a laminate. The prepared laminate is pressed at 25° C. through a 100 MPa pressure plate for 10 minutes to manufacture an all-solid-state secondary battery. The solid electrolyte layer is sintered during the pressing process to improve battery characteristics.
[0215] Examples 7 to 10
[0216] An all-solid-state secondary battery was manufactured in the same manner as in Example 6, except that in the positive electrode layer, the solid electrolyte prepared in Example 1 was changed to the solid electrolyte prepared in Examples 2 to 5.
[0217] Examples 11 to 14
[0218] An all-solid-state secondary battery was manufactured in the same manner as in Example 6, except that in the positive electrode layer, the solid electrolyte prepared in Example 1 was changed to the solid electrolyte prepared in Examples 5A-1 to 5A-4.
[0219] Comparative Examples 8 to 14
[0220] An all-solid-state secondary battery was manufactured in the same manner as in Example 6, except that in the positive electrode layer, the solid electrolyte prepared in Example 1 was changed to the solid electrolytes prepared in Comparative Examples 1 to 7.
[0221] Evaluation Example 1: Measurement of ion conductivity
[0222] The powder of each solid electrolyte prepared in Examples 1 to 5 was placed in a mold having a diameter of 10 mm and pressed at a pressure of 350 MPa to form a sheet (disk). Both surfaces of the sheet were covered with an indium (In) film to prepare a sample for measuring ionic conductivity. The impedance of the prepared sample was measured using a potentiostat (AUTOLAB PGSTAT30, manufactured by Metrohm Autolab Co. Ltd.) to draw a Nyquist diagram, and the ionic conductivity at 25° C. was measured from the Nyquist diagram.
[0223] The measured ionic conductivity is shown in Table 3.
[0224] Table 3
[0225] Example Ionic conductivity (mS / cm) Example 1 3.9 Example 2 3.7 Example 3 4.1 Example 4 3.6 Example 5 3.4
[0226] As shown in Table 3, the solid electrolytes prepared in Examples 1 to 5 each had an excellent ion conductivity of 1 mS / cm or more.
[0227] Evaluation Example 2: XRD Analysis
[0228] The XRD spectra of the solid electrolytes prepared in Example 1 and Comparative Examples 1 to 5 were measured, and the results are shown in Figures 1A to 1C middle. Figure 1B and 1C for Figure 1A An enlarged view of a portion of .
[0229] refer to Figure 1A , it can be found that the solid electrolyte of Example 1 has an argyrodite crystal structure similar to those of Comparative Examples 1 to 5. Figure 1B and 1C As shown in, in the XRD spectrum of the solid electrolyte of Example 1, there is a first peak at 29.82°2θ corresponding to the (311) crystal plane, and a second peak at 31.18°2θ corresponding to the (222) crystal plane. Compared with the peaks corresponding to the solid electrolytes of Comparative Examples 1 to 5, the peak shifts of the first peak and the second peak are observed at a low angle of about 0.06° to about 0.48°.
[0230] In addition, in the XRD spectrum of the solid electrolyte of Example 1, there is a third peak at 44.62°2θ corresponding to the (422) crystal plane, a fourth peak at 47.47°2θ corresponding to the (511) crystal plane, and a fifth peak at 51.99°2θ corresponding to the (440) crystal plane. Compared with the peaks corresponding to the solid electrolytes of Comparative Examples 1 to 5, the peak shifts of the third peak, the fourth peak, and the fifth peak are observed at a low angle of about 0.11°2θ to about 0.4°2θ.
[0231] Evaluation Example 3: Evaluation of high voltage stability
[0232] The charge and discharge characteristics of the all-solid-state secondary batteries of Examples 6 to 10 using the solid electrolytes of Examples 1 to 5 and the all-solid-state secondary batteries of Comparative Examples 8 to 12 using the solid electrolytes of Comparative Examples 1 to 5 were evaluated by a charge-discharge test.
[0233] The battery was charged at a constant current of 0.1C for about 10 hours until the battery voltage was 4.25V, and charged at a constant voltage of 4.25V until the current was 0.05C, and then rested for 10 minutes. Then, the battery was discharged at a constant current of 0.1C for about 10 hours until the battery voltage was 2.5V, and rested for 10 minutes. This process is called the "first cycle".
[0234] Subsequently, the battery was charged at a constant current of 0.1C for about 10 hours until the battery voltage was 4.25V, and placed at 45°C for about 40 hours, and then rested for 10 minutes. Then, the battery was discharged at a constant current of 0.1C for about 10 hours until the battery voltage was 2.5V, and rested for 10 minutes. This process is called the "second cycle".
[0235] After that, the battery was charged at a constant current of 0.1C for about 10 hours until the battery voltage was 4.25V, and charged at a constant voltage of 4.25V until the current was 0.05C, and then rested for 10 minutes. Then, the battery was discharged at a constant current of 0.1C for about 10 hours until the battery voltage was 2.5V, and rested for 10 minutes. This process is called the "third cycle".
[0236] The capacity recovery rate was calculated by Equation 1 and is shown in Table 4 and Figure 2 middle.
[0237] Equation 1
[0238] Capacity recovery rate (%) = (discharge capacity at the third cycle / discharge capacity at the first cycle) × 100%
[0239] Table 4
[0240] Example Capacity recovery rate (%) Example Capacity recovery rate (%) Example 6 94.4 Comparative Example 8 80.2 Example 7 89.0 Comparative Example 9 73.9 Example 8 92.4 Comparative Example 10 73.5 Example 9 99.9 Comparative Example 11 73.7 Example 10 99.6 Comparative Example 12 60.5
[0241] As shown in Table 4, it can be found that the capacity recovery rate of the all-solid-state secondary batteries of Examples 6 to 10 is significantly improved compared with those of the all-solid-state secondary batteries of Comparative Examples 8 to 12. From the results, it can be found that the oxidation stability of the solid electrolyte used in the all-solid-state secondary batteries of Examples 6 to 10 is significantly improved compared with the oxidation stability of the solid electrolyte used in the all-solid-state secondary batteries of Comparative Examples 8 to 12.
[0242] Evaluation Example 4: Evaluation of Cycle Characteristics and High Voltage Stability
[0243] The charging and discharging characteristics of the all-solid-state secondary batteries manufactured in Example 10 and Comparative Example 13 were evaluated by the following charging-discharging test.
[0244] The evaluation of the cycle characteristics was performed in the same manner as in the high voltage stability evaluation until the third cycle. The "fourth cycle" was performed as follows. The battery was charged at a constant current of 0.33C for about 3 hours until the battery voltage was 4.25V, and charged at a constant voltage of 4.25V until the current was 0.1C, and then rested for 10 minutes. Then, the battery was discharged at a constant current of 0.33C for about 3 hours until the battery voltage was 2.5V, and rested for 10 minutes.
[0245] Thereafter, charging and discharging were performed in the same manner as in the fourth cycle, and the cycle characteristics were evaluated. Figure 3 In , the initial charge and discharge are for the first cycle, and the recovery capacity is the discharge value in the third cycle.
[0246] The charge-discharge curves of the all-solid-state batteries of Example 10 and Comparative Example 13 are shown in Figure 3 middle.
[0247] like Figure 3 As shown in , it can be found that in the all-solid-state secondary battery of Example 10, charging and discharging are performed reversibly, which allows an increased capacity recovery rate, improved cycle characteristics, and improved high voltage stability compared to the all-solid-state secondary battery of Comparative Example 13.
[0248] The discharge capacity changes of the all-solid-state batteries of Example 10 and Comparative Example 13 according to the number of cycles are shown in Figure 4 middle.
[0249] like Figure 4 As shown in , it can be found that in the all-solid-state secondary battery of Example 10, unlike the all-solid-state secondary battery of Comparative Example 13, the cycle characteristics are improved.
[0250] Evaluation Example 5: Evaluation of high voltage stability and cycle characteristics
[0251] The charge and discharge characteristics of the all-solid-state secondary battery of Example 10 using the solid electrolyte of Example 5 and the all-solid-state secondary battery of Comparative Example 14 using the solid electrolyte of Comparative Example 7 were evaluated by the following charge-discharge test.
[0252] The battery was charged at a constant current of 0.1 C for about 10 hours until the battery voltage was 4.25 V, and charged at a constant voltage of 4.25 V until the current was 0.05 C, and then rested for 10 minutes. Then, the battery was discharged at a constant current of 0.05 C for about 20 hours until the battery voltage was 2.5 V, and rested for 10 minutes ("first cycle").
[0253] Subsequently, the battery was charged at a constant current of 0.1C for about 10 hours until the battery voltage was 4.25V, and then left at 60°C for about 10 days. Subsequently, the battery was discharged at a constant current of 0.05C for about 20 hours until the battery voltage was 2.5V ("second cycle").
[0254] After that, the battery was charged at a constant current of 0.1C for about 10 hours until the battery voltage was 4.25V, charged at a constant voltage of 4.25V until the current was 0.05C, and then rested for 10 minutes. Then, the battery was discharged at a constant current of 0.05C for about 20 hours until the battery voltage was 2.5V ("third cycle").
[0255] The charge-discharge curves of the all-solid-state batteries of Example 10 and Comparative Example 14 are shown in Figure 5 The capacity recovery rate is calculated by equation 1 and is shown in Figure 6 middle.
[0256] Equation 1
[0257] Capacity recovery rate (%) = (discharge capacity at the third cycle / discharge capacity at the first cycle) × 100%
[0258] like Figure 5 As shown in , in the all-solid-state secondary battery of Example 10, unlike the all-solid-state secondary battery of Comparative Example 14, charging and discharging are reversibly performed during the first cycle and the second cycle. Therefore, it can be found that the cycle characteristics are improved. In addition, as Figure 6 As shown in , the capacity recovery rate of the all-solid-state secondary battery of Example 10 is 87%, which is higher than the capacity recovery rate of 76% of the all-solid-state secondary battery of Comparative Example 14. Therefore, it can be found that the high voltage stability is improved.
[0259] Furthermore, the high voltage stability and cycle characteristics of the all-solid-state secondary batteries of Examples 11 to 17 were evaluated according to the same evaluation methods as in the all-solid-state secondary battery of Example 10 using the solid electrolyte of Example 5.
[0260] As a result, it was found that the all-solid-state secondary batteries of Examples 11 to 17 exhibited the same high-voltage oxidation stability as that of the all-solid-state secondary battery of Example 10.
[0261] According to one aspect, a solid electrolyte having excellent ion conductivity and improved high voltage stability can be provided. When such a solid electrolyte is used, an electrochemical cell having improved capacity recovery rate and cycle characteristics can be provided.
[0262] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for limiting purposes. The description of features, aspects, or advantages in each embodiment should be considered to be applicable to other similar features, aspects, or advantages in other embodiments. Although one or more embodiments have been described with reference to the accompanying drawings, it will be understood by those of ordinary skill in the art that various changes in form and detail may be made therein without departing from the spirit and scope as defined by the appended claims.
Claims
1. A solid electrolyte, comprising: A compound having a thiogermanate crystal structure and represented by Formula 1 Formula 1 Li a M x PS b Br c X d Wherein, in Formula 1, M is Fe, Mg, Ca, Ag, Cu, Zr, Zn, or a combination thereof; X is Cl; and 0 ≤ x < 1, 5 ≤ (a + x) < 7, 5 ≤ a ≤ 6, 4 ≤ b ≤ 6, and 0 < (c + d) < 1.
2. The solid electrolyte according to claim 1, wherein In Formula 1, 5 ≤ (a + x) ≤ 6.
3. The solid electrolyte according to claim 1, wherein In Formula 1, 0 ≤ x ≤ 0.
07.
4. The solid electrolyte according to claim 1, wherein the compound is a compound represented by the following Formula 2: <Formula 2> Li a M x PS b (Br) c (Cl) d in, In Formula 2, M is Fe, Mg, Ca, Ag, Cu, Zr, Zn, or a combination thereof, 0 ≤ x ≤ 0.07, 5 ≤ a ≤ 6, 4 ≤ b ≤ 6, 0 < (c + d) < 1, and 5 ≤ (a + x) ≤ 6.
5. The solid electrolyte according to claim 1, wherein the compound is a compound represented by the following Formula 3: <Formula 3> (Li 1-x1 M x1 ) 7-y PS 6-y (Br 1-x2 (Cl) x2 ) y in, In Formula 3, M is Fe, Mg, Ca, Ag, Cu, Zr, Zn, or a combination thereof, and 0 ≤ x1 < 1, 0 < x2 < 1, and 0 ≤ y ≤ 2.
6. The solid electrolyte according to claim 1, wherein the compound represented by Formula 1 is a compound represented by the following Formula 4 or a compound represented by the following Formula 5: <Formula 4> (Li 1-x1 Na x1 ) 7-y P.S. 6-y (Br 1-x2 (Cl) x2 ) y in, In Formula 4, x1 = 0, 0 < x2 < 1, and 0 ≤ y ≤ 2, <Formula 5> (Li 1-x1 K x1 ) 7-y PS 6-y (Br 1-x2 (Cl) x2 ) y Wherein, in Formula 5, x1 = 0, 0 < x2 < 1, and 0 ≤ y ≤ 2.
7. The solid electrolyte according to claim 1, wherein when analyzed by X-ray diffraction using Cu Kα radiation, the compound of Formula 1 has a first peak at 29.82° ± 0.05° 2θ corresponding to the (311) crystal plane and a second peak at 31.18° ± 0.05° 2θ corresponding to the (222) crystal plane.
8. The solid electrolyte according to claim 1, wherein When analyzed by X-ray diffraction using Cu Kα radiation, the compound of Formula 1 has a third peak at 44.62° ± 0.11° 2θ corresponding to the (422) crystal plane, a fourth peak at 47.47° ± 0.12° 2θ corresponding to the (511) crystal plane, and a fifth peak at 51.99° ± 0.1° 2θ corresponding to the (440) crystal plane.
9. The solid electrolyte according to claim 1, wherein the solid electrolyte has an ionic conductivity of 1 millisiemens per centimeter or greater at room temperature.
10. An electrochemical cell, comprising: A positive electrode layer; A negative electrode layer; And A solid electrolyte layer between the positive electrode layer and the negative electrode layer, Wherein at least one of the positive electrode layer and the solid electrolyte layer comprises the solid electrolyte according to any one of claims 1-9.
11. The electrochemical cell of claim 10, wherein: The positive electrode layer comprises a solid electrolyte, and the solid electrolyte comprises a compound having a thiogermanate crystal structure and represented by Formula 1: Formula 1 Li a M x PS b Br c X d Wherein, in Formula 1, M is Fe, Mg, Ca, Ag, Cu, Zr, Zn, or a combination thereof, X is Cl, 0 ≤ x < 1 and 5 ≤ (a + x) < 7, 5 ≤ a ≤ 6, 4 ≤ b ≤ 6, and 0 < (c + d) < 1.
12. The electrochemical cell of claim 10, wherein the positive electrode layer comprises a positive electrode active material, a solid electrolyte, and a conductive material, and the content of the solid electrolyte in the positive electrode layer is about 2 parts by weight to about 70 parts by weight based on 100 parts by weight of the positive electrode active material.
13. The electrochemical cell of claim 10, wherein after the all-solid-state secondary battery is charged to 4.25 volts at 45°C or 60°C and discharged, the electrochemical cell has a capacity retention of 70% or more during a first cycle.
14. The electrochemical cell of claim 10, wherein the negative electrode layer comprises a negative electrode current collector, and a first negative electrode active material layer comprising a negative electrode active material on the negative electrode current collector, and The negative electrode active material includes a carbon negative electrode active material, a metal negative electrode active material, a metalloid negative electrode active material, or a combination thereof.
15. The electrochemical cell of claim 14, wherein the carbon negative electrode active material comprises amorphous carbon, crystalline carbon, or a combination thereof, and The metal negative electrode active material or the metalloid negative electrode active material includes Au, Pt, Pd, Si, Ag, Al, Bi, Sn, Zn, or a combination thereof.
16. The electrochemical cell of claim 14, further comprising: a second negative electrode active material layer between the negative electrode current collector and the first negative electrode active material layer, between the solid electrolyte layer and the first negative electrode active material layer, or a combination thereof, The second negative electrode active material layer is a metal layer including lithium or a lithium alloy.
17. The electrochemical cell of claim 10, wherein the positive electrode layer comprises a positive electrode active material, and the positive electrode active material is a lithium transition metal oxide having a layered crystal structure, a lithium transition metal oxide having an olivine crystal structure, a lithium transition metal oxide having a spinel crystal structure, or a combination thereof.
18. The electrochemical cell of claim 10, wherein the electrochemical cell is an all-solid-state secondary battery.
Citation Information
Patent Citations
Cathode for lithium ion secondary battery, and lithium ion secondary battery
KR1020160064942A
Method and device for rendering timed text and graphics in virtual reality video
KR1020190140946A